The Influence of OrganicFertilizer and Dosage of NPK Multiple Fertilizer on Growth and Yield of Cucumber (Cucumis sativus L. - Sri Rustianti; Sunarti Sunarti; Khairil Anwar (University of Prof. Dr. Hazairin, SH, 2021)
The administration of organic fertilizer to provide nutrients for plants is insufficient. It is because organic fertilizers contain low nutrients. Thus, plants need more nutrients that are obtainable from the administration of inorganic fertilizers. This research aimed to find: the effects of the best types of organic fertilizers on the growth and yields of cucumbers; the effects of the dose of NPK compound fertilizers on the growth and yields of cucumber; and the effects of interaction between the various types of organic fertilizer and the dose of NOK compound fertilizers on the growth and yields of cucumber. This research used Factorial Randomized Block Design with three replications. The first factor was the Various Types of Organic Fertilizers consisting of Without Organic Fertilizers, Goat Manure, and Petrogranik Organic Fertilizers. The second factor was the dose of NPK compound fertilizers of 200, 250, and 300 kg/ha. Analysis of variance was then performed and followed by Duncan Multiple Range Test (DMRT). Research results indicated that the treatment with various types of organic fertilizers provided significant effects on all observed variables; in the treatment with the Dose of NPK compound fertilizers provided significant effects on the plant and fruit weights and did not provide significant effects on other variables; interaction of various types of organic fertilizers and the dose of NPK compound fertilizers did not provide significant effects on all observed variables; Various types of organic fertilizer, such as goat manure provided the best growth and yields; the Dose of NPK compound fertilizers of 250kg/ha provided the best growth and yields of cucumbers.